Accounting Treatment of Fixed Assets Based on PSAK No. 16/2018 At Union Metal Industry Medan - Yulifati Laoli; Rosmaida Tambun; Dameria Naibaho (Syntax Corporation Indonesia, 2022)
Union Metalindo Jaya Medan is a company engaged in construction services for buildings, roads, parks, residential areas (real estate), and electrical installations or can also be declared a general contractor. To achieve the company’s goals that have been set, companies need various production factors to support and facilitate operational activities, namely fixed assets. This study aimed to determine whether the accounting treatment of fixed assets at Union Metalindo Jaya Medan followed the Statement of Financial Accounting Standards No. 16 of 2018. In writing this research, the nature of the research used is a case study. With this method, the facts regarding the accounting treatment policy for tangible fixed assets are obtained by observing and analyzing a research object problem that occurs in a research location on the existing suitability and then drawing conclusions from the problems studied. After conducting research, the authors concluded that the company in the accounting treatment of fixed assets is still not following PSAK No. 16 2018. Therefore, companies must consider many things in making policies on recording the acquisition price of fixed assets and expenditures after the acquisition of fixed assets. , Depreciation of fixed assets, as well as the presentation of fixed assets in the financial statements.